Isolation and application of purple non-sulfur bacteria for sulfide and organic matter removal - Lê, Thị Kim Chi; Lê, Mậu Bình; Nguyễn, Ngọc Khánh; Hoàng, Hà Mỹ Á; Huy, Nguyễn Đức (Hue University Journal of Science: Natural Science, 2026)
The study reported the isolation of purple non-sulfur photosynthetic bacteria (PNSB) from water and sediment samples collected from shrimp ponds in Cua Tung commune, Ben Hai, Cua Viet, Quang Tri province to evaluate the sulfide and organic matter removal capabilities. As a result, two strains, designated QH07 and QH35, demonstrated sulfide removal efficiencies of 88.86% and 86.05%, respectively. Additionally, two strains, designated QH09 and QH42, exhibited organic matter removal efficiencies of 59.40% and 56.09%, respectively, after 7 days of cultivation. All four strains were Gram-negative, forming colonies that ranged from circular to perfectly round, with pigmentation varying from yellow-brown to orange-red and purple-red. Molecular identification revealed that strain QH07 belonged to Cereibacter genus and was named Cereibacter sp. QH07, while the isolate QH35 belonged to the genus Rhodobacter, and designated as Rhodobacter sp. QH35. Strains QH09 and QH42 were classified under the genus Rhodopseudomonas, and named Rhodopseudomonas faecalis QH09 and R. palustris QH42, respectively. The current isolates exhibiting strong activity in H2S and organic matter removal are important materials to produce bioinoculant products for treatment residual H2S and organic matter in shrimp pond water.